Pengaruh Pemberian Ekstrak Etanol Bit Merah (Beta vulgaris L.) terhadap Struktur Histologis Ginjal Mencit (Mus musculus) Akibat Paparan Minyak Kelapa Sawit Pemanasan Berulang - Fitri Febrianti Ramadhan; . Muthmainah; Vitri Widyaningsih (Nexus Biomedika, 2014)
Background: One of plants with abundant antioxidant compounds is red beet (Beta vulgaris L.). That antioxidant compounds can be found in betalain pigment, ?-karoten, vitamin A, vitamin C, vitamin E, flavonoid, mineral Cu, Mn, Zn and selenium. This research was conducted to prove the nefroprotective effect and the optimal dose of ethanol extract of red beet which can prevent renal cells damage of mice induced by deep frying palm oil. Methods: This research was laboratory experimental research. Samples were thirty Swiss webster male mice, 2-3 months old and 20 grams of each weight divided into 5 groups randomly, each groups have six mice. Normal control group (KKn) wasnt given any treatments, only aquades. The second group (KP) was induced 0.06 ml/ 20 g weight deep frying palm oil orally and aquades every day for 14 days that can cause renal cells damaging. KP1, KP2, and KP3 were given nephroprotector treatment of ethanol red beet extract with dosage 5.6 ml/ 20 g weight, 11.2 ml/ 20 g weight, and 22.4 ml/ 20 g weight and then after an hour induced 0.06 ml/ 20 g weight frying palm oil orally every day for 14 days. Renal histological imaging were assessed by the sum of the cell nucleus picnosis, cariorecsis, and cariolysis. Data were analyzed using One-Way ANOVA and followed by Post Hoc Multiple Comparisons test. (? = 0.05) Results: One-way ANOVA test showed that the value of p was < 0.001. Mean of each group were KKn (8.671.27), KP (44.631.31), KP1 (33.881.15), KP2 (22.751.70), and KP3 (12.791.38). Post hoc multiple comparisons test results showed there was significant. Mean difference of KP-KP1, KP1-KP2, and KP2-KP3 were respectively 10.75, 11.12, and 9.96. Conclusions: The nefroprotective effect and the optimal dose of ethanol extract of red beet can prevent renal cells damaging of mice induced by deep frying palm oil. Keywords: red beet, deep frying palm oil, histology of renal